Implementing Project-Based Learning to Enhance Senior High School Students’ Digital Citizenship Literacy - Kusnadi, Edi; Tutun Nurlaela; Wafa Nisa Audry; Nanda Nur Azzahra; Moh. Yusril Fhadil (PT Inovasi Pratama Internasional, 2026)
This study examines the effectiveness of a Project-Based Learning (PjBL) model in improving digital citizenship literacy among Indonesian senior high school students. Grounded in the integration of Pancasila and Civic Education (PPKn) with digital citizenship competencies, the research responds to evidence that students’ digital skills are uneven, with strengths in safety and etiquette but weaknesses in content creation and critical participation. A quasi-experimental quantitative design with a nonequivalent control group was employed, involving Grade XI students from two public senior high schools in Jakarta. The experimental group received PjBL-based instruction on digital citizenship issues, while the control group was taught using conventional expository methods. Digital citizenship literacy covering digital access, communication, etiquette, and rights and responsibilities was measured using a validated Likert-scale test administered as pretest and posttest. Data were analyzed using descriptive statistics, normalized gain scores, and independent samples t-tests. The findings (illustrative) indicate that PjBL yields higher gains in digital citizenship literacy than traditional instruction, particularly in digital communication and etiquette, which are widely recognized as core dimensions of digital citizenship in contemporary civics education. The study discusses pedagogical implications for integrating PjBL into PPKn and other related subjects to prepare students as ethical, critical, and participatory digital citizens